MicroRNA‐146a targets PRKCE to modulate papillary thyroid tumor development. Issue 2 (18th September 2013) - Zhang, Xiaoping; Li, Dan; Li, Maoquan; Ye, Meng; Ding, Lanbao; Cai, Haidong; Fu, Da; Lv, Zhongwei
Abstract : MicroRNAs are single‐stranded noncoding RNAs composed of approximately 22 nucleotides that suppress gene expression by selectively binding via base‐pairing to the complementary 3′‐untranslated region (3′‐UTR) of messenger RNA transcripts. Protein kinase C epsilon (PKCε) is an important modulating member of the transducing Ras/Raf‐1 signal pathway; a computational search revealed miR‐146a putatively binds to the 3'‐UTR of the PRKCE gene, and thus decreasing PKCε expression. Moreover, PKCε inhibits mitochondrial apoptosis and is associated with the Bcl family. However, it has been previously reported that miR‐146a expression in papillary thyroid carcinoma (PTC) is slightly elevated. Thus, we hypothesized that because miR‐146a expression depends on nuclear factor kappaB (NF‐κB) activation and NF‐κB expression is elevated in PTC, miR‐146a is potentially upregulated in PTC via negative feedback of NF‐κB, and thus suppressing PKCε expression. In our study, we investigated whether overexpression of miR‐146a, a tumor‐suppressing‐miR, in PTC cells decreases cell survival and induces apoptosis. Luciferase reporter assay analysis confirmed the direct binding of miR‐146a and PRKCE 3′‐UTR. Specific overexpression of exogenous miR‐146a significantly decreased PKCε levels in PTC cell line NPA‐187 and increased apoptosis. Additionally, using stably expressing miR‐146a thyroid carcinoma cells to establish subcutaneous tumors, the tumor growth exhibited significant inhibition. Our study confirmed the tumor‐suppressing role of miR‐146a in thyroid carcinoma cells and contributes to the knowledge regarding modulation of Ras/Raf‐1 signal transduction and apoptosis via PKCε targeted by miR‐146a in PTC; moreover, our findings confirmed that miR‐146a is involved in the feedback system of the classical NF‐κB signal pathway in PTC. Abstract : What's new? The identification of marked changes in microRNA expression in papillary thyroid carcinoma (PTC) has provided an opportunity to gain additional insight into the molecular mechanisms that contribute to the disease. Of particular interest has been miR‐146a, which is reported here to result in decreased protein kinase C epsilon (PKCε) levels and increased apoptosis when overexpressed in PTC cells. Its overexpression was also found to inhibit tumor growth in a mouse xenograft model. The findings lend support to the idea that miR‐146a counteracts the oncogenic potential of PKCε.